2015
DOI: 10.1128/mbio.00630-15
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Evolution of Hypervirulent Klebsiella pneumoniae

Abstract: Highly invasive, community-acquired Klebsiella pneumoniae infections have recently emerged, resulting in pyogenic liver abscesses. These infections are caused by hypervirulent K. pneumoniae (hvKP) isolates primarily of capsule serotype K1 or K2. Hypervirulent K1 isolates belong to clonal complex 23 (CC23), indicating that this clonal lineage has a specific genetic background conferring hypervirulence. Here, we apply whole-genome sequencing to a collection of K. pneumoniae isolates to characterize the phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
317
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(336 citation statements)
references
References 78 publications
13
317
2
4
Order By: Relevance
“…The CC23 K1 HV K. pneumoniae strains were significantly more closely related to each other than to other K1 strains, indicating that they likely disseminated globally from a distinct variant (235). However, these CC23 K1 HV K. pneumoniae strains were more closely related to the K1 reference strain used in this study than they were to other K. pneumoniae strains (235). It has been suggested that the increased virulence associated with K1 and K2 HV strains may be due to the concurrent carriage of several virulence-associated factors, namely, hypercapsule and the siderophore aerobactin (see below), compared to their presence in other strains (227).…”
Section: Capsulementioning
confidence: 99%
See 2 more Smart Citations
“…The CC23 K1 HV K. pneumoniae strains were significantly more closely related to each other than to other K1 strains, indicating that they likely disseminated globally from a distinct variant (235). However, these CC23 K1 HV K. pneumoniae strains were more closely related to the K1 reference strain used in this study than they were to other K. pneumoniae strains (235). It has been suggested that the increased virulence associated with K1 and K2 HV strains may be due to the concurrent carriage of several virulence-associated factors, namely, hypercapsule and the siderophore aerobactin (see below), compared to their presence in other strains (227).…”
Section: Capsulementioning
confidence: 99%
“…For example, in a mouse liver abscess model, K1 and K2 strains that lacked a hypercapsule, rmpA, and aerobactin were avirulent (227). In fact, HV CC23 strains all carried the genes for two siderophores as well as RmpA on a large plasmid as well as a genomic island with several differences from other K. pneumoniae strains (235). On the other hand, some work suggests that the presence of the K1/K2 serotypes themselves, rather than hypercapsule, is responsible for increased virulence, as typical capsule-producing K1/K2 strains are not significantly less virulent than hypercapsule-producing K1/K2 strains (229).…”
Section: Capsulementioning
confidence: 99%
See 1 more Smart Citation
“…The K type and O type of K. pneumoniae both have important clinical and epidemiological significance (8, 12, 13). K1 clonal complex 23 is a newly emerged hypervirulent clade, which causes pyogenic liver abscesses with septic ocular or central nervous system complications (8,14,15). Likewise, O1 is associated with hypervirulent strains that cause pyogenic liver abscess (12).…”
mentioning
confidence: 99%
“…12 However, the study was limited in that it was based on a single strain of each serotype, and thus the relevance of this study's results in regards to other K. pneumoniae strains and serotypes must be explored. In addition, many studies indicate an association between K. pneumoniae serotypes and their severity of infection, 10,14,15 and between production of CPS and antibiotic resistance. 16 Further studies, including serotype switching, are warranted in order to more fully understand the effects of the K antigen or serotype on virulence and other features.…”
mentioning
confidence: 99%